Stopnja avtonomije timov v podjetjih - Lužar, Barbara (Teorija in praksa, 2013)
Over the past few years, teamwork has been enforced as a specific way of organising work with many positive impacts on companies. The article examines teamwork and its complexity on the basis of the degree of team autonomy or team independence. An empirical survey conducted in June 2011 shows that a large share of Slovenian companies included in the survey have formally organised teams. The empirical findings also reveal a low degree of teams' autonomy in terms of their influence on subject matter, and especially regarding their strategic decisions within the companies. The article ends with some suggestions for further research on teams and their autonomy.
Keywords: Autonomy; Avtonomija; Enterprises; Organizacija dela; Organization of labour; Podjetja; skupinsko delo; Team work; Timsko delo